CALCULATIONS OF CURRENTS IN THE UPWELLING REGION ALONG SOlJTH-CENTRAL VIETNAMESE COAST, USING THREE DIMENSIONS (3-D) NONLINEAR MODEL - Long, Bui Hong; Chung, Tran Van (Vietnam Journal of Marine Science and Technology, 2009)
Currelll regime in th e stro ng upwelling region along Southern CentralVietnamese coast is simulared by solving rhe shallow water wave propagation model using finite element method during southwest monsoon (August 2005) and northeast monsoon (Nov. 2005). The initial calcularion results is good. especially the adaptabiliry of the model to the hard boundcuy, calcularion grid and the stabiliry. The calculation grid is also established in detail according ro th e changing oftopograplty. The calculation results can be Summarized as follows:- During SW monsoon: the velocity of horizontal currents changes slowly and can reach a maximum value of 39 cm/s in ENE direction (60°). The direction of horizontal currents is similarly from surface to the 10m layer- During NE monsoon: Because th ere is 110 significant difference between the velocities of the two wind fields at the selected time periods (the maximum SW monsoon wind velocity is 9.8m/s, average is 8.O m/s, while that of the NE monsoon wind velocity is 10.2m/s; average is 7.9m/s), the horizontal current field oftwo wind fields also shows, no obvious difference. incase of northeast wind field, from the surface to the 10m layer there is almost 110 change in velocity of horizontal currents, the peak velocity reaches 39cm/s, direction is 242°